A Single Polymer Artificial Muscle Having Dual‐Mode Contractibility, Temperature Sensibility, and Trainability through Enthalpy Change. Issue 5 (20th February 2019) - Zhu, Shanshan; Hu, Jinlian; Zhang, Yuanchi
Abstract: Artificial muscles (AMs) have high demand in many fields like robotics, medical devices, sensors, and actuators as well as prosthesis. To achieve what a natural muscle can do for humans in AMs, an ideal material should be cheap, soft, and have both isotonic and isometric contractions, high energy density, sensibility, and trainability. However, only a single function of AM, isotonic contraction, is considered in most existing studies, while other critical functions are always neglected. Moreover, current AMs are normally made of either hard metals or polymer composites, or special structures typically twisted coils of thermal expansion polymers. Here a single polymer artificial muscle (SPAM) with natural muscle molecular structures is reported to perform both isotonic and isometric contractions (dual‐mode), where spring structure is similar to titin and semicrystal likes actin. This SPAM can sense the surrounding temperature due to a crystal phase where enthalpy‐battery is installed. Then the trainability is proved by structural evolution which leads to contraction responsive to stimulated conditions with longitudinal strokes higher than 29%, and a specific work up to 473 J kg −1, respectively. This single soft polymer realizes significant multifunctions of an AM without any complicated structure design and composite system. Abstract : Dual‐mode muscle contractions with temperature stimulation are achieved using a single polymer without complicated structures and control systems. Three batteries of thermal expansion, entropy change, and enthalpy change are comparatively investigated, where enthalpy proves predominant in contraction control. Adjusting crystallization behaviors achieves temperature sensibility and performance trainability of the single polymer artificial muscle, like in a real muscle.